Sri Lanka's Sources of Growth - Braiton, Nombulelo (IMF Working Papers; Working Paper ;, 2007)
This paper uses the growth accounting framework to assess Sri Lanka's sources of growth. It finds that while labor was the dominant factor contributing to growth in the 1980s, labor's contribution declined over time and was overtaken, to a large extent, by total factor productivity (TFP) and, to a lower extent, by physical and human capital accumulation. A higher growth path over the medium term will depend on securing a stable political and macroeconomic environment; implementing structural reforms necessary to improve productivity and efficiency of investment; attaining fiscal consolidation; and creating space for the private sector.